Design of a Decoupling Control System for pH and TDS in Hydroponics - Putri, Ina Rahmawati; Siswojo, Bambang; Rusli, Mochammad (Faculty of Engineering, Universitas Brawijaya, 2026)
Hydroponics was a sustainable cultivation method that optimized land and water use efficiency. The stability of the nutrient solution in this system was strongly influenced by pH and Total Dissolved Solids (TDS) parameters, which were closely interrelated. Changes in pH values could affect TDS concentration, and vice versa, creating coupled dynamics that complicated precise control. This study applied a decoupling control strategy that separated interaction effects so that pH and TDS could be controlled more independently. The system was developed using a pH sensor, a TDS sensor, an Arduino Uno microcontroller, and three peristaltic pumps for adding pH up, pH down, and nutrient solutions. The results showed that the decoupling control system in simulation-maintained pH stability with a rise time of 6.04 s, a settling time of 31.04 s, an overshoot of 9.59%, and a steady-state error of 0, while TDS achieved a rise time of 84.79 s, a settling time of 161.45 s, and a steady-state error of 0.0005%. The hardware implementation demonstrated similar performance with a pH rise time of 42.62 s, a settling time of 46 s, an overshoot of 10%, a steady-state error of 0.68%, and TDS with a rise time of 62.35 s, a settling time of 91 s, an overshoot of 2.40%, and a steady-state error of 0.72%. This study proved that the decoupling method provided more optimal nutrient control performance in hydroponic systems.